The Actuality of a World: What Ceases Not to Be Written - Ronen, Ruth (Filozofski vestnik, 2022)
“There is no longer any world,” wrote the late philosopher Jean-Luc Nancy in 1993, and in this paper, the sense of this loss of world is analysed in terms of the modal notions of necessity, impossibility, and possibility. Modal differentiation can illuminate what constitutes the sense of actuality in a world, and hence, what it is that has been lost regarding this actuality of being in a world. Modal thinking does not rely on knowledge of the true state of affairs, nor on having a constant grasp on necessity: modal thinking enables us to discern the actual by way of the relations between necessity, possibility, and impossibility. It is on the basis of these relations that a mode of rethinking actuality is suggested. In order to pursue this line of thought, I rely on Jacques Lacan’s understanding of modalities as writing operations, concentrating mostly on certain sections from his Seminar XXI (1973–1974), wherein he refers to Aristotelian modal logic and mentions the analytic philosopher Jaakko Hintikka (as one of Aristotle’s commentators). This ternary relation between Aristotle, Hintikka, and Lacan suggests a different outlook on the actual being-such of a world. The being-such of a world, its actuality, is understood as a contingency (what ceases not to be written), a possibility emerging from the relation between what is declared necessary and what is impossible. The paper shows the implications of such a modal understanding of actuality, as demonstrated in Lacan’s view of human sexuality and sexual difference.